Hole transport material and preparation method thereof, solar cell and optoelectronic device
By using hole transport polymers connected to the conjugated group, the thermal stability and moisture influence of hole transport materials in perovskite solar cells are solved, the efficiency and stability of the device are improved, the energy level matching is optimized, and the cost is reduced.
Patent Information
- Application Number
- CN202510588832.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-07
- Publication Date
- 2025-08-01
AI Technical Summary
In existing perovskite solar cells, hole transport materials such as spiro-OMeTAD and PTAA have problems such as poor thermal stability, susceptible to moisture, and low hole mobility, which affect device performance and stability.
A hole transport polymer is used to form a periodic electron donor-acceptor alternating structure through thiourea groups and conjugated groups, enhancing interface stability and energy level matching, reducing costs, reducing side reactions, and inhibiting ion migration.
The photoelectric conversion efficiency and stability of perovskite solar cells are improved, the energy level matching between the transport layer and perovskite is optimized, the hole extraction capability is enhanced, and the dependence on dopants is reduced.
Smart Images

Figure CN120399203A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of photovoltaic cells, and particularly to a hole transport material, a preparation method thereof, a solar cell, and an optoelectronic device. Background Art
[0002] Perovskite solar cells have received extensive attention due to their long carrier diffusion length, high absorption coefficient, adjustable bandgap, compatibility with various preparation methods, and simple preparation methods. Among them, the hole transport layer (HTL) is an important component, and its function is to extract the holes generated by the perovskite layer and transport them to the electrode, and to prevent the backflow of the battery.
[0003] Currently, the perovskite hole transport materials are mainly 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), and these materials have relatively high power conversion efficiency. In recent years, small molecule materials of selective self-assembled monolayers (SAMs) have emerged and developed rapidly. SAMs help to improve the crystallization quality of perovskite thin films, reduce the recombination of photo-generated carriers at the interface, and reduce the defect state density by improving the interface contact and charge transport kinetics, thereby improving the device efficiency and stability.
[0004] However, spiro-OMeTAD is prone to thermal degradation in its original state, and its dopants such as lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 4-tert-butylpyridine (tBP) have hygroscopicity and easy evaporation respectively, thus affecting the stability of perovskite materials and devices; PTAA is not a good barrier for ion diffusion, it is susceptible to moisture, mechanical failure and peeling are likely to occur at the interface, and the hole mobility of PTAA is relatively low, which limits its device performance as an HTL, and the hole transport in PTAA and the hole extraction ability at the interface need to be improved by dopants such as molybdenum oxide (MoO3); the devices with a hole transport layer based on extremely thin SAMs still have the problem of poor thermal stability under high temperature conditions. High temperature may cause the chemical bond formed between the SAM molecular anchoring group and the substrate to break, affecting the interface charge extraction and resulting in device degradation or failure. In addition, traditional SAM materials tend to aggregate, affecting the photovoltaic performance of the device. Summary of the Invention
[0005] Based on this, it is necessary to provide a hole transport material, a preparation method thereof, a solar cell, and an optoelectronic device, which can effectively passivate the defects in the perovskite film, reduce non-radiative recombination, reduce the loss of carriers, and regulate the crystallization rate of the perovskite film, improve the quality of the perovskite film, and further improve the photoelectric conversion efficiency of the perovskite solar cell; without the need to add additional dopants, reduce costs, reduce side reactions, and the structure of the polymer long chain and the interaction between the thiocarbamoyl group and the perovskite can stabilize the lattice and inhibit ion migration, thereby improving the efficiency and stability of the perovskite solar cell.
[0006] In the first aspect of the present application, a hole transport material is provided, and the hole transport material includes a hole transport polymer, and the hole transport polymer has a repeating unit represented by formula (I):
[0007]
[0008] Formula (I);
[0009] In formula (I): * represents a bonding site; Y represents a single bond, a sulfur atom, an oxygen atom, a nitrogen atom, or does not exist; X represents a single bond, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted aryl group having 5 or 6 ring-forming atoms, or a substituted or unsubstituted heteroaryl group having 5 or 6 ring-forming atoms.
[0010] In some embodiments, X is selected from one of the following structures:
[0011] , , , , , , .
[0012] In some embodiments, the hole transport polymer is a homopolymer formed by the repeating unit represented by formula (I).
[0013] In some embodiments, in the hole transport polymer, the number of the repeating units represented by formula (I) is an integer from 3 to 10000000.
[0014] In some embodiments, the weight-average molecular weight M w of the hole transport polymer is from 1000 g / mol to 2000000 g / mol.
[0015] The second aspect of the present application provides a method for preparing a hole transport material, the preparation method comprising the following steps: S1. A dibromo aromatic amine compound undergoes nucleophilic substitution reactions with an N-(tert-butoxycarbonyl)-α-bromo amine compound and a thiocyanate successively to obtain an intermediate compound; S2. The intermediate compound undergoes a polymerization reaction to obtain a hole transport polymer; wherein, the dibromo aromatic amine has the structure shown in formula (II):
[0016]
[0017] Formula (II);
[0018] The N-(tert-butoxycarbonyl)-α-bromo amine compound has the structure shown in formula (III):
[0019]
[0020] Formula (III);
[0021] The intermediate compound has the structure shown in formula (IV):
[0022]
[0023] Formula (IV);
[0024] The hole transport polymer has a repeating unit shown in formula (I):
[0025]
[0026] Formula (I);
[0027] In formula (I)-(IV), * represents a bonding site; Y represents a single bond, a sulfur atom, an oxygen atom, a nitrogen atom, or does not exist; X represents a single bond, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted aryl group having 5 to 6 ring-forming atoms, or a substituted or unsubstituted heteroaryl group having 5 to 6 ring-forming atoms.
[0028] In some embodiments, step S1 specifically comprises the following steps: S11. A dibromo aromatic amine compound undergoes a nucleophilic substitution reaction with an N-(tert-butoxycarbonyl)-α-bromo amine compound to obtain a first intermediate; S12. The first intermediate removes the tert-butoxycarbonyl group under acid catalysis to obtain a second intermediate; S13. The second intermediate undergoes a nucleophilic substitution reaction with a thiocyanate to obtain a third intermediate, which is the intermediate compound; wherein, the first intermediate has the structure shown in formula (V):
[0029]
[0030] Formula (V);
[0031] The second intermediate has the structure shown in formula (VI):
[0032]
[0033] Formula (VI).
[0034] In some embodiments, step S2 specifically includes the following steps: S21. The intermediate compound reacts with a tert-butoxycarbonyl protecting agent to introduce a tert-butoxycarbonyl group, obtaining a fourth intermediate; S22. After the fourth intermediate undergoes a polymerization reaction, the tert-butoxycarbonyl group is removed by acid catalysis, obtaining a hole-transporting polymer; wherein, the fourth intermediate has the structure shown in formula (VII):
[0035]
[0036] Formula (VII).
[0037] In some embodiments, the polymerization reaction is carried out under the action of a nickel catalyst and a ligand.
[0038] The third aspect of the present application provides a solar cell, which includes a hole-transporting layer, and the hole-transporting layer includes the hole-transporting material provided in the first aspect above or the hole-transporting material prepared by the preparation method provided in the second aspect above.
[0039] The fourth aspect of the present application provides an optoelectronic device, which includes a hole-transporting layer, and the hole-transporting layer includes the hole-transporting material provided in the first aspect above or the hole-transporting material prepared by the preparation method provided in the second aspect above.
[0040] Compared with the traditional technology, the present application has at least the following beneficial effects:
[0041] The hole-transporting material provided by the present application has a repeating unit shown in formula (I) in the hole-transporting polymer, and the repeating unit forms a periodic electron donor-acceptor alternating structure (D-A pair) by connecting a thiourea group and a conjugated group. On the one hand, the amino group and the thiocarbonyl group in the thiourea group can interact with the undercoordinated Pb in the perovskite 2+ and the organic cations, and the S atom of the thiourea group has a weak interaction with I - (a new peak appears at 260 cm⁻¹ in the Raman spectrum). The thiourea group has a strong reducing effect on I2. They can synergistically passivate the defects in the perovskite film, which can not only reduce non-radiative recombination and reduce the loss of carriers, but also anchor the material on the perovskite surface, improve the interface stability, and thus improve the efficiency and stability of the device.
[0042] On the other hand, due to the introduction of the thiourea group, the material of the thiourea group type has a relatively large dipole moment, which can effectively block electrons and extract holes. At the same time, there is an intramolecular hydrogen bond between the amino group and the thiocarbonyl group in the thiourea group (distance ≈ 2.8 Å). The planar configuration formed thereby enhances the π-π stacking. The thiocarbonyl group, as a strong electron-withdrawing group, and the amino group, as an electron-rich group, form an intramolecular D-A pair, which raises its HOMO energy level (ultraviolet photoelectron spectroscopy shows that its HOMO energy level has increased by about 0.3 eV), making it closer to the valence band top energy level of the perovskite, thereby optimizing the energy level matching degree between the transport layer and the perovskite and enhancing its hole extraction ability.
[0043] Therefore, the hole transport material provided in this application does not require the additional addition of a dopant, which reduces the cost and reduces side reactions. Moreover, the structure of the polymer long chain and the interaction between the thiourea group and the perovskite can stabilize the crystal lattice and inhibit ion migration, thereby improving the efficiency and stability of the perovskite solar cell. Description of the Drawings
[0044] Figure 1 It is a schematic flowchart of the preparation method of the hole transport material in an embodiment of this application.
[0045] Figure 2 It is a schematic comparison diagram of the contact angles of the perovskite solution on the hole transport layers formed by the hole transport materials TM1 and TM2 in Example 1 and Example 2 of this application.
[0046] Figure 3 It is an energy level comparison diagram of the hole transport materials TM1 and TM2 in Example 1 and Example 2 of this application.
[0047] Figure 4 It is a schematic cross-sectional comparison diagram of the scanning electron microscope (SEM) of the hole transport layers formed by the hole transport materials TM1 and TM2 and the perovskite layer in Example 1 and Example 2 of this application.
[0048] Figure 5 It is an ultraviolet absorption spectrogram of the hole transport materials TM1 and TM2 in Example 1 and Example 2 of this application.
[0049] Figure 6 It is an I-V test curve diagram of the perovskite solar cells respectively prepared based on the hole transport materials TM1 and TM2 in Example 1 and Example 2 of this application.
[0050] Figure 7 It is an efficiency decay diagram of the perovskite solar cells respectively prepared based on the hole transport materials TM1 and TM2 in Example 1 and Example 2 of this application. Detailed Embodiments
[0051] Reference will now be made in detail to embodiments of the present application, one or more examples of which are described below. Each example is provided by way of explanation and not limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to the present application without departing from the scope or spirit of the present application. For example, features illustrated or described as part of one embodiment can be used in another embodiment to yield a still further embodiment.
[0052] Accordingly, it is intended that the present application cover such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in the following detailed description or are apparent therefrom. Those of ordinary skill in the art should understand that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0053] In the present application, among the technical features described in an open-ended manner, there are included closed technical solutions composed of the listed features, as well as open technical solutions containing the listed features.
[0054] In the present application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when the range refers to integers, it includes each integer between the minimum and maximum values of the range. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.
[0055] If there is no special indication, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions.
[0056] If there is no special indication, all technical features and optional technical features of the present application can be combined with each other to form new technical solutions.
[0057] If there is no special indication, all steps of the present application can be carried out in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out in sequence, or can also include steps (b) and (a) carried out in sequence. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b), and (c), or can also include steps (a), (c), and (b), or can also include steps (c), (a), and (b), etc.
[0058] Unless otherwise specified, the terms "comprising" and "including" used in this application are open-ended and may also be closed-ended. For example, the terms "comprising" and "including" may mean that other components not listed may also be included or comprised, or that only the listed components are included or comprised.
[0059] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0060] Term Explanation:
[0061] Unless otherwise stated or in case of contradiction, the terms or phrases used herein have the following meanings:
[0062] The term "alkyl" refers to a saturated hydrocarbon group containing primary (normal) carbon atoms, or secondary carbon atoms, or tertiary carbon atoms, or quaternary carbon atoms, or a combination thereof. A phrase containing this term, for example, "C1-C9 alkyl", refers to an alkyl group containing 1 to 9 carbon atoms, which may, each time it appears, independently of one another, be a C1 alkyl group, a C2 alkyl group, a C3 alkyl group, a C4 alkyl group, a C5 alkyl group, a C6 alkyl group, a C7 alkyl group, a C8 alkyl group or a C9 alkyl group. Suitable examples include, but are not limited to: methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3) and octyl (-(CH2)7CH3).
[0063] The term "aryl" refers to an aromatic hydrocarbon group derived by removing one hydrogen atom from an aromatic ring compound, which may be a monocyclic aryl group, or a fused-ring aryl group, or a polycyclic aryl group, and for a polycyclic ring system, at least one is an aromatic ring system. Suitable examples include, but are not limited to: benzene, biphenyl, naphthalene, anthracene, phenanthrene, pyrene, triphenylene and their derivatives.
[0064] The term "ring-forming atom" refers to an atom that directly participates in forming a ring in the cyclic structure of an aryl or heteroaryl group. For a polycyclic structure, the number of ring-forming atoms in each independent ring is calculated separately.
[0065] The term "heteroaryl" refers to a group in which at least one carbon atom in an aryl group is replaced by a non-carbon atom, and the non-carbon atom can be an N atom, an O atom, an S atom, etc. Suitable examples include, but are not limited to: furan, benzofuran, thiophene, benzothiophene, pyrrole, pyrazole, triazole, imidazole, oxazole, oxadiazole, thiazole, tetrazole, indole, carbazole, pyrroloimidazole, pyrrolopyrrole, thiophenopyrrole, thiophenothiophene, furanopyrrole, furanofuran, thiophenofuran, benzisoxazole, benzisothiazole, benzimidazole, pyridine, pyrazine, pyridazine, pyrimidine, triazine, quinoline, isoquinoline, phthalazine, quinoxaline, phenanthridine, perimidine, quinazoline, and quinazolinone.
[0066] The first aspect of the present application provides a hole-transporting material, which includes a hole-transporting polymer having a repeating unit represented by formula (I):
[0067]
[0068] Formula (I).
[0069] In formula (I): * represents a bonding site. Y represents a single bond, a sulfur atom, an oxygen atom, a nitrogen atom, or is absent. X represents a single bond, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted aryl group having 5 or 6 ring-forming atoms, or a substituted or unsubstituted heteroaryl group having 5 or 6 ring-forming atoms.
[0070] In the hole-transporting material provided by the present application, since the hole-transporting polymer has a repeating unit represented by formula (I), and the repeating unit forms a periodic electron donor-acceptor alternating structure (D-A pair) by connecting a thiourea group and a conjugated group. On the one hand, the amino group and the thiocarbonyl group in the thiourea group can interact with the undercoordinated Pb 2+ and organic cations in the perovskite, and the S atom of the thiourea group has a weak interaction with I - (a new peak appears in the Raman spectrum at 260 cm -1 ), and the thiourea group has a strong reducing effect on I2. They can cooperate to passivate the defects in the perovskite film, which can not only reduce non-radiative recombination and reduce the loss of carriers, but also anchor the material on the perovskite surface, improve the interface stability, and thus improve the efficiency and stability of the device.
[0071] On the other hand, due to the introduction of thiourea groups, the dipole moment of thiourea group-type materials is larger, which can effectively block electrons and extract holes; at the same time, the amino group and the thiocarbonyl group in the thiourea group have hydrogen bonding in the molecule (distance ≈ 2.8Å), and the planar configuration formed thereby enhances the π-π stacking. The thiocarbonyl group as a strong electron-withdrawing group and the amino group as an electron-rich group form an intramolecular DA pair, which increases its HOMO energy level (ultraviolet photoelectron energy spectrum shows that its HOMO energy level increases by about 0.3eV), making it closer to the top energy level of the valence band of the perovskite, thereby optimizing the energy level matching between the transport layer and the perovskite and enhancing its hole extraction ability.
[0072] Therefore, the hole transport material provided by the present application does not require the addition of additional dopants, which reduces costs and side reactions. The structure of the long polymer chain and the interaction between the thiourea group and the perovskite can stabilize the lattice and inhibit ion migration, thereby improving the efficiency and stability of perovskite solar cells.
[0073] In some embodiments, X is selected from one of the following structures:
[0074] 、 、 、 、 、 、 Thus, as the linking group between the thiocarbamoyl group and the conjugated group, X is selected as an aryl or heteroaryl group. This not only utilizes the conjugation of the aryl or heteroaryl group itself to further improve the degree of conjugation of the hole transport polymer, thereby raising the HOMO energy level of the hole transport material to bring it closer to the valence band top energy level of the perovskite material, optimizing energy level matching and improving hole mobility, but also utilizes the π-π stacking effect to enhance the intermolecular interaction force, promote the orderly arrangement of the polymer molecules, reduce the barrier to charge transfer, and thus improve the photoelectric conversion efficiency of the solar cell.
[0075] In some embodiments, X represents a C1-C5 alkyl group. Controlling the alkyl chain's carbon number to 1-5 ensures an appropriate spacing between the thiocarbamoyl group and the conjugated group, avoiding steric hindrance and thereby facilitating effective extension of the conjugated system and delocalization of π electrons, thus optimizing hole transport properties. It also imparts flexibility to the polymer, improving its film-forming properties and enhancing device stability. Furthermore, the introduction of a short-chain alkyl group helps adjust the polymer's solubility, making it more soluble in common solvents, facilitating material processing and device fabrication. Furthermore, X represents a C1 alkyl group.
[0076] In some embodiments, the hole transport polymer is a homopolymer formed by repeating units represented by formula (I).
[0077] Exemplarily, the hole-transporting polymer is at least one selected from homopolymers formed by repeating units represented by the following formula (I):
[0078] ;
[0079] wherein, n is the number of repeating units represented by formula (I), and m is the number of carbon atoms of the alkyl group. Further, m is an integer from 1 to 5.
[0080] In some other embodiments, the hole-transporting polymer is a copolymer formed by the repeating units represented by formula (I) and other repeating units.
[0081] It can be understood that the present application places no limitation on other repeating units. Exemplarily, the other repeating units can be triphenylamine group, carbazole group, benzocarbazole group or phenothiazine group.
[0082] In some of these embodiments, in the hole-transporting polymer, the number of repeating units represented by formula (I) is an integer from 3 to 100,000. Exemplarily, the number of repeating units represented by formula (I) can be, but is not limited to, 3, 4, 5, 10, 20, 25, 50, 100, 200, 500, 1000, 2000, 5000, 10,000, 20,000, 50,000, 100,000.
[0083] In some of these embodiments, the weight-average molecular weight M w of the hole-transporting polymer is from 1000 g / mol to 2,000,000 g / mol. Exemplarily, the weight-average molecular weight M w of the hole-transporting polymer can be, but is not limited to, 1000 g / mol, 5000 g / mol, 10,000 g / mol, 50,000 g / mol, 100,000 g / mol, 500,000 g / mol, 1,000,000 g / mol, 2,000,000 g / mol.
[0084] The second aspect of the present application provides a preparation method of a hole-transporting material, as Figure 1 shown, the preparation method includes the following steps:
[0085] S1. The dibromo aromatic amine compound undergoes nucleophilic substitution reactions with N-(tert-butoxycarbonyl)-α-bromoamine compound and thiocyanate successively to obtain an intermediate compound.
[0086] S2. The intermediate compound undergoes a polymerization reaction to obtain a hole-transporting polymer.
[0087] wherein, the dibromo aromatic amine has a structure represented by formula (II):
[0088]
[0089] Formula (II).
[0090] The N-(tert-butoxycarbonyl)-α-bromoamine compounds have the structure shown in Formula (III):
[0091]
[0092] Formula (III).
[0093] The intermediate compound has the structure shown in Formula (IV):
[0094]
[0095] Formula (IV).
[0096] The hole-transporting polymer has a repeating unit shown in Formula (I):
[0097]
[0098] Formula (I).
[0099] In Formulas (I)-(IV): * represents a bonding site. Y represents a single bond, a sulfur atom, an oxygen atom, a nitrogen atom, or does not exist. X represents a single bond, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted aryl group having 5 or 6 ring-forming atoms, or a substituted or unsubstituted heteroaryl group having 5 or 6 ring-forming atoms.
[0100] In some of these embodiments, step S1 specifically includes the following steps:
[0101] S11. A nucleophilic substitution reaction occurs between a dibromo aromatic amine compound and an N-(tert-butoxycarbonyl)-α-bromoamine compound to obtain a first intermediate.
[0102] S12. The first intermediate removes the tert-butoxycarbonyl group under acid catalysis to obtain a second intermediate.
[0103] S13. A nucleophilic substitution reaction occurs between the second intermediate and a thiocyanate to obtain a third intermediate, which is the intermediate compound.
[0104] Among them, the first intermediate has the structure shown in Formula (V):
[0105]
[0106] Formula (V).
[0107] The second intermediate has the structure shown in Formula (VI):
[0108]
[0109] Formula (VI).
[0110] In some of these embodiments, in step S21, the nucleophilic substitution reaction is carried out under base catalysis.
[0111] In some of these embodiments, step S2 specifically includes the following steps:
[0112] S21. The intermediate compound reacts with a tert-butoxycarbonyl protecting agent to introduce a tert-butoxycarbonyl group, obtaining a fourth intermediate.
[0113] S22. After the fourth intermediate undergoes a polymerization reaction, the tert-butoxycarbonyl group is removed by acid catalysis, obtaining a hole-transporting polymer.
[0114] Among them, the fourth intermediate has the structure shown in Formula (VII):
[0115]
[0116] Formula (VII).
[0117] In some of these embodiments, in step S21, the tert-butoxycarbonyl protecting agent is selected from one of di-tert-butyl dicarbonate, 2-(tert-butoxycarbonyloxyimino)-2-phenylacetonitrile, tert-butyl chloroformate, and tert-butyl azidoformate.
[0118] In some of these embodiments, the molar ratio of the dibromoaromatic amine compound to the N-(tert-butoxycarbonyl)-α-bromoamine compound is 1:1.
[0119] In some of these embodiments, the molar ratio of the second intermediate to the thiocyanate is 1:2.
[0120] In some of these embodiments, the polymerization reaction is carried out under the action of a nickel catalyst and a ligand. Thus, the nickel catalyst provides a metal active center, the ligand coordinates with the nickel metal center to form a nickel complex, and they cooperate with each other to form a catalytic active center, which promotes the specific occurrence of a debromination coupling polymerization reaction between monomers to form a hole-transporting polymer.
[0121] In some specific embodiments, when the nickel catalyst is Ni(cod)2, the ligand is 2,2'-bipyridine and 1,8-cyclooctadiene.
[0122] The third aspect of the present application provides a solar cell, which includes a hole-transporting layer, and the hole-transporting layer includes the hole-transporting material provided in the first aspect above or the hole-transporting material prepared by the preparation method provided in the second aspect above.
[0123] In some of these embodiments, the solar cell is a perovskite solar cell. The perovskite solar cell includes a perovskite layer disposed on a hole transport layer. The present application does not limit the specific structure of the solar cell; in a specific embodiment, the solar cell is one of a perovskite single-junction cell, a perovskite / perovskite tandem cell, a perovskite / crystalline silicon tandem cell, a perovskite / organic tandem cell, and a perovskite / copper indium gallium selenide tandem cell.
[0124] The hole transport layer can be prepared by conventional methods in the art, including but not limited to sol-gel method, spin coating method, spraying method, doctor blade method, and slot-die coating method.
[0125] In some of its embodiments, the hole transport layer is prepared by the following method: dissolving the above hole transport material in an organic solvent to prepare a hole transport layer solution; then coating the hole transport layer solution on a substrate and annealing to obtain the hole transport layer. Among them, the concentration of the hole transport material in the hole transport layer solution is 0.1 mg / mL to 10 mg / mL; the organic solvent is chloroform, chlorobenzene, toluene, methanol, ethanol, or a mixture thereof.
[0126] In some of these embodiments, the chemical formula of the material of the perovskite layer satisfies ABX3 or A2CDX6, where A is an inorganic, organic, or organic / inorganic hybrid cation, which can be at least one of MA, FA, and Cs; B is an inorganic, organic, or organic / inorganic hybrid cation, which can be at least one of Pb and Sn; C is an inorganic, organic, or organic / inorganic hybrid cation, commonly Ag + ; D is an inorganic, organic, or organic / inorganic hybrid cation, which can be bismuth cation Bi 3+ 、antimony cation Sb 3+ 、and indium cation In 3+ at least one of them; X is an inorganic, organic, or organic / inorganic hybrid anion, which can be at least one of Br and I. The band gap of the perovskite layer is 1.20 eV to 2.30 eV.
[0127] The perovskite layer can be prepared by conventional technical means in the art, or can be prepared by the following method: weighing the material of the perovskite layer, dissolving it in a solvent (such as dimethylformamide (DMF), dimethyl sulfoxide (DMSO), etc.), stirring evenly, filtering, and taking the supernatant; covering the supernatant on the prepared electron transport layer or hole transport layer, and the covering method can be spin coating with a spin coater, where the rotation speed can be 500 rpm to 5000 rpm, the spin coating time can be 5 to 50 seconds, annealing is performed after spin coating, the annealing temperature can be 80°C to 150°C, the annealing time can be 0 min to 60 min, and the perovskite layer is obtained after annealing.
[0128] The thickness of the perovskite layer can be any thickness used in the art. Optionally, the thickness of the perovskite layer is 200 nm to 1000 nm.
[0129] In some embodiments, the solar cell is an organic solar cell.
[0130] In some embodiments, the solar cell is a tandem solar cell. The solar cell further includes a substrate, and a hole transport layer is disposed on the substrate.
[0131] Generally speaking, a tandem solar cell structurally includes a substrate, a hole transport layer, a perovskite layer, an electron transport layer, and an electrode layer in sequence; that is, incident light passes through the substrate, the hole transport layer, the perovskite layer, the electron transport layer, and the electrode layer in sequence.
[0132] In some embodiments, the substrate is selected from one of crystalline silicon cells, conductive glass, and flexible conductive films.
[0133] In some embodiments, the crystalline silicon cell includes one of a passivated emitter and rear contact cell (PERC cell), a tunnel oxide passivated contact cell (TOPCon cell), a crystalline silicon heterojunction solar cell (HJT cell), and a back contact cell (IBC cell).
[0134] In some embodiments, the conductive glass has a certain transparency. The conductive glass is usually composed of a glass substrate and an oxide thin film (abbreviation TCO) conductive layer. Commonly used TCOs include, but are not limited to, the following materials: fluorine-doped tin oxide (FTO), indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), indium zinc oxide (IZO). The conductive glass is usually any conductive glass used in the art. The conductive glass can be commercially obtained. The conductive glass needs to be cleaned before use, for example, ultrasonically cleaned with a cleaning agent, deionized water, ethanol, etc.
[0135] In some embodiments, the flexible conductive film includes one of indium tin oxide (ITO) film, fluorine-doped tin oxide (FTO) film, aluminum-doped zinc oxide (AZO) film, boron-doped zinc oxide (BZO) film, and indium zinc oxide (IZO) film.
[0136] In some embodiments, the material of the electron transport layer includes [6,6]-phenyl C 61 butyric acid methyl ester (PC61BM), [6,6]-phenyl C 71 butyric acid methyl ester (PC71BM), fullerene C 60 (C 60 ) fullerene C 70 (C 70) One or more of tin dioxide (SnO2), zinc oxide (ZnO), titanium dioxide (TiO2), derivatives of the above substances, and materials obtained by doping or passivation.
[0137] The electron transport layer can be prepared by conventional methods in the art or by the following method: Dissolve the electron transport layer material in an organic solvent (such as chlorobenzene, dichlorobenzene, toluene, xylene) to prepare a solution of the electron transport layer material with a concentration range of 5 mg / mL to 50 mg / mL. Then cover the surface of the conductive glass or perovskite layer, and the covering method can be spin coating using a spin coater, where the rotation speed can be 500 rpm to 5000 rpm, the spin coating time can be 5 to 50 seconds, and after spin coating, annealing is carried out. The annealing temperature can be 80°C to 50°C, and the annealing time can be 5 min to 60 min. After annealing, the electron transport layer is obtained.
[0138] The thickness of the electron transport layer can be any thickness used in the art. Optionally, the thickness of the electron transport layer is 10 nm to 100 nm.
[0139] The electrode layer can use any electrode in the art. Optionally, the material of the electrode layer is an organic or inorganic or organic-inorganic hybrid conductive material, including but not limited to the following materials: Ag, Cu, C, Au, Al. The electrode layer can be prepared by evaporation coating.
[0140] The thickness of the electrode layer can be any thickness used in the art. Optionally, the thickness of the electrode layer is 10 nm to 200 nm.
[0141] The solar cell provided by this application can be used in power-consuming devices such as vehicles, ships, or aircraft, etc., but is not limited thereto.
[0142] One embodiment of this application provides a power-consuming device, which can be but is not limited to mobile phones, tablets, laptop computers, electric toys, electric tools, battery cars, electric vehicles, ships, spacecraft, etc. Among them, the electric toys can include fixed or mobile electric toys, such as game consoles, electric vehicle toys, electric ship toys, and electric aircraft toys, etc. The spacecraft can include airplanes, rockets, space shuttles, and spaceships, etc.
[0143] The fourth aspect of this application provides an optoelectronic device, which includes a hole transport layer, and the hole transport layer includes the hole transport material provided in the first aspect above or the hole transport material prepared by the preparation method provided in the second aspect above.
[0144] In some of these embodiments, the optoelectronic device can be a field-effect transistor, a light-emitting diode, a photodetector, etc.; in the field-effect transistor, the hole-transporting material is used as an organic semiconductor material, and in the light-emitting diode and the photodetector, it is used as a hole-transporting layer and a hole-injecting layer, or as an interface modification layer on the basis of the original hole-transporting layer and hole-injecting layer.
[0145] The present application will be further described below in conjunction with specific examples and comparative examples.
[0146] For those not specifying the specific technology or conditions in the examples, the technology or conditions described in the literature in this field or according to the product specifications are followed. For reagents or instruments not indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0147] Example 1
[0148] Hole-transporting material:
[0149] The hole-transporting material is a hole-transporting polymer.
[0150] (1) Dissolve 10 g of bis(4-bromophenyl)amine and 8.31 g of N-Boc-4-bromoaniline in 100 mL of N,N-dimethylformamide (DMF), add 8.44 g of K2CO3 for base catalysis, heat to 60 °C and stir for 12 hours for a nucleophilic substitution reaction. After monitoring the reaction to completion by thin-layer chromatography, wait for it to cool to room temperature, pour it into 300 mL of ice water, and filter to obtain 12.98 g of a white solid, the first intermediate GM1.
[0151] The structural formula of GM1 is shown as follows:
[0152]
[0153] GM1.
[0154] The NMR test data of GM1 are as follows: 1 H NMR(400MHz, CDCl3, ppm):9.05 (br, 1H),7.50(d, 2H), 7.39 (d, 4H), 7.29 (d, 2H), 7.18 (d, 4H), 1.50(s, 9H); 13 C NMR (400MHz, CDCl3, ppm): 153.3, 140.2, 141.5, 136.6, 135.6, 134.8, 132.4, 121.0,25.2.
[0155] (2) Dissolve 12.98 g of GM1 in 60 mL of dioxane hydrochloride solution (4 M), stir at room temperature for 3 hours for acid-catalyzed removal of the tert-butoxycarbonyl group, filter to obtain 8.9 g of white solid second intermediate GM2. The structural formula of GM2 is as follows:
[0156]
[0157] GM2.
[0158] The NMR test data of GM2 are as follows: 1 H NMR(400MHz, DMSO, ppm): 7.60 (d, 2H), 7.42(d, 4H), 7.36 (d, 2H), 7.28 (d, 4H), 3.0(br, 4H); 13 C NMR (400 MHz, DMSO, ppm): 141.6, 138.8, 136.8, 136.2, 135.6, 132.4, 129.2, 126.0.
[0159] (3) Dissolve 8.9 g of GM2 in 130 mL of tetrahydrofuran (THF), add 3.79 g of KSCN, heat to 70 °C and reflux for 12 hours for nucleophilic substitution reaction. Cool to room temperature, add 100 mL of water, extract twice with 100 mL of ethyl acetate. The organic phase is dried with anhydrous sodium sulfate, filtered and concentrated to obtain 6.08 g of crude yellow oily third intermediate GM3, which is the intermediate compound. The structural formula of GM3 is as follows:
[0160]
[0161] GM3.
[0162] The NMR test data of GM3 are as follows: 1 H NMR(400MHz, CDCl3, ppm): 11.96(br, 1H), 8.29(br, 2H), 7.54 (s, 2H), 7.39 (d, 2H), 7.33 (d, 2H), 5.31 (t, 2H), 4.23 (t,2H); 13 C NMR (400 MHz, CDCl3, ppm): 179.1, 138.5, 136.8, 135.8, 135.2, 128.9,124.0, 52.0, 40.1.
[0163] (4) Dissolve 6.08 g of GM3 in a mixed solution of 30 mL of THF and 30 mL of water. Add 2.70 g of Na2CO3 and 2.74 g of di-tert-butyl dicarbonate, and react at room temperature for 12 hours. Add 30 mL of water, and extract twice with 60 mL of ethyl acetate. Dry the organic phase with anhydrous sodium sulfate, filter and concentrate the organic phase, and purify by flash column chromatography to obtain 6.69 g of a yellow solid, the fourth intermediate GM4, with the structural formula as follows:
[0164]
[0165] GM4.
[0166] (5) Weigh 3.82 g of Ni(cod)2, 1.89 g of 2,2'-bipyridine, and 1.81 g of 1,8-cyclooctadiene in a glove box, add them to 60 mL of DMF, heat to 80 °C, and react for half an hour. This solution is denoted as A; dissolve 6.69 g of GM4 in 15 mL of DMF, and slowly drip this solution into the heated A solution under a nitrogen atmosphere. Polymerize at 80 °C for 24 hours, then cool to room temperature, add 60 mL of dilute hydrochloric acid (1 M), add 100 mL of dichloromethane and extract twice. After liquid separation, dry the organic phase with anhydrous sodium sulfate and concentrate. Add 120 mL of methyl tert-butyl ether to the residue, stir for 30 min, filter to obtain 2.99 g of a white solid. Then dissolve the white solid in 15 mL of a dioxane hydrochloride solution (4 M), stir at room temperature for 24 hours, filter to obtain a white solid. Dissolve the white solid in 15 mL of water, adjust the pH to 8 - 9 with ammonia water, extract twice with 30 mL of dichloromethane, dry the organic phase with anhydrous sodium sulfate, filter and concentrate. Add 15 mL of methyl tert-butyl ether and stir for 2 hours, filter to obtain 1.21 g of a white solid TM1, which is the hole-transporting polymer.
[0167] The structural formula of the hole-transporting polymer is as follows:
[0168]
[0169] TM1;
[0170] Among them, n = 127, and the weight-average molecular weight M w is 40513.
[0171] Solar cell:
[0172] Weigh 0.5 mg of the hole transporting material and dissolve it in 1 mL of chlorobenzene to obtain the hole transporting layer solution; then spin-coat the hole transporting layer solution (60 μL) onto the ITO conductive glass at a speed of 3000 rpm / s, anneal it at 100 °C for 5 minutes, and cool it to room temperature to form the hole transporting layer with a thickness of 7 nm; sequentially prepare the perovskite layer, the electron transporting layer, and the electrode layer on the hole transporting layer to obtain a solar cell, where the perovskite layer includes FA 0.95 Cs 0.05 PbI3 material, and the electron transporting layer includes C 60 material, and the electrode layer includes Ag metal.
[0173] Example 2
[0174] In this example, the preparation method of the hole transporting material and the solar cell is basically the same as that in Example 1, except that:
[0175] The hole transporting material is TM2, and the structural formula of TM2 is as follows:
[0176]
[0177] TM2;
[0178] where n = 492, and the weight-average molecular weight M of the hole transporting polymer w is 132348.
[0179] Example 3
[0180] In this example, the preparation method of the hole transporting material and the solar cell is basically the same as that in Example 1, except that:
[0181] The hole transporting material is TM3, and the structural formula of TM3 is as follows:
[0182]
[0183] TM3;
[0184] where n = 131, m = 1, and the weight-average molecular weight M of the hole transporting polymer w is 43099.
[0185] Example 4
[0186] In this example, the preparation method of the hole transporting material and the solar cell is basically the same as that in Example 1, except that:
[0187] The hole transporting material is TM4, and the structural formula of TM4 is as follows:
[0188]
[0189] TM4;
[0190] Among them, n = 43, m = 1, and the weight-average molecular weight M of the hole-transporting polymer w is 17802.
[0191] Example 5
[0192] In this example, the preparation methods of the hole-transporting material and the solar cell are basically the same as those in Example 1, except that:
[0193] The hole-transporting material is TM5, and the structural formula of TM5 is shown as follows:
[0194]
[0195] TM5;
[0196] Among them, n = 136, m = 1, and the weight-average molecular weight M of the hole-transporting polymer w is 42568.
[0197] Example 6
[0198] In this example, the preparation methods of the hole-transporting material and the solar cell are basically the same as those in Example 1, except that:
[0199] The hole-transporting material is TM6, and the structural formula of TM6 is shown as follows:
[0200]
[0201] TM6;
[0202] Among them, n = 67, and the weight-average molecular weight M of the hole-transporting polymer w is 28207.
[0203] Example 7
[0204] In this example, the preparation methods of the hole-transporting material and the solar cell are basically the same as those in Example 1, except that:
[0205] The hole-transporting material is TM7, and the structural formula of TM7 is shown as follows:
[0206]
[0207] TM7;
[0208] Among them, n = 113, and the weight-average molecular weight M of the hole-transporting polymer w is 38985.
[0209] Example 8
[0210] In this embodiment, the preparation method of the hole transport material and the solar cell is basically the same as that of Example 1, except that:
[0211] The hole transport material is TM8, and the structural formula of TM8 is as follows:
[0212]
[0213] TM8;
[0214] where n = 61, and the weight-average molecular weight M of the hole transport polymer w is 24583.
[0215] Example 9
[0216] In this embodiment, the preparation method of the hole transport material and the solar cell is basically the same as that of Example 1, except that:
[0217] The hole transport material is TM9, and the structural formula of TM9 is as follows:
[0218]
[0219] TM9;
[0220] where n = 84, and the weight-average molecular weight M of the hole transport polymer w is 32508.
[0221] Example 10
[0222] In this embodiment, the preparation method of the hole transport material and the solar cell is basically the same as that of Example 1, except that:
[0223] The hole transport material is TM10, and the structural formula of TM10 is as follows:
[0224]
[0225] TM10;
[0226] where n = 36, and the weight-average molecular weight M of the hole transport polymer w is 12708.
[0227] Example 11
[0228] In this embodiment, the preparation method of the hole transport material and the solar cell is basically the same as that of Example 1, except that:
[0229] In step (5), for the prepared hole transport polymer TM1, n = 15, and the weight-average molecular weight M w = 4785.
[0230] Example 12
[0231] In this embodiment, the preparation method of the hole transport material and the solar cell is basically the same as that of Example 1, except that:
[0232] In step (5), n of the prepared hole transport polymer TM1 is 1201, and the weight average molecular weight M w = 383119.
[0233] Comparative Example 1
[0234] Hole transport material:
[0235] Commercially available PTAA material (manufacturer: Sigma-Aldrich). Among them, the weight average molecular weight M w of PTAA is 300000.
[0236] Solar cell:
[0237] Weigh 0.5 mg of the hole transport material and dissolve it in 1 mL of chlorobenzene to obtain a hole transport layer solution; then spin-coat the hole transport layer solution (60 μL) on the ITO conductive glass at a speed of 3000 rpm / s, anneal it at 100 °C for 5 minutes, and cool it to room temperature to form a hole transport layer with a thickness of 7 nm; sequentially prepare a perovskite layer, an electron transport layer, and an electrode layer on the hole transport layer to obtain a solar cell, where the perovskite layer includes FA 0.95 Cs 0.05 PbI3 material, the electron transport layer includes C 60 material, and the electrode layer includes Ag metal.
[0238] Comparative Example 2
[0239] Hole transport material:
[0240] A PTAA material (manufacturer: Sigma-Aldrich) and thiosemicarbazide with a mass ratio of 1:1. Among them, the weight average molecular weight M w of PTAA is 300000.
[0241] Solar cell:
[0242] Weigh 0.5 mg of the hole transport material and dissolve it in 1 mL of chlorobenzene to obtain a hole transport layer solution; then spin-coat the hole transport layer solution (60 μL) on the ITO conductive glass at a speed of 3000 rpm / s, anneal it at 100 °C for 5 minutes, and cool it to room temperature to form a hole transport layer with a thickness of 7 nm; sequentially prepare a perovskite layer, an electron transport layer, and an electrode layer on the hole transport layer to obtain a solar cell, where the perovskite layer includes FA 0.95 Cs 0.05 PbI3 material, the electron transport layer includes C60 Material, the electrode layer includes Ag metal.
[0243] Performance test
[0244] (1) Contact angle test
[0245] The surface of the hole transport layer prepared in the above-mentioned examples and comparative examples was subjected to a contact angle test using a perovskite solution. Among them, the perovskite material in the perovskite solution is FA 0.95 Cs 0.05 PbI3, and the concentration of the perovskite solution is 1 mg / mL. The test results are shown in Table 1 and Figure 2 . As Figure 2 shown, the contact angle of the perovskite solution on the TM1 hole transport layer is 14.81°, and the contact angle on the TM2 is 13.87°; these are much smaller than the contact angle of the traditional PTAA material, indicating that the wettability of the TM1 and TM2 hole transport materials synthesized in this scheme for the perovskite solution has been greatly improved.
[0246] (2) Energy level test
[0247] The HOMO energy levels of the hole transport material TM1 in Example 1 and the hole transport material TM2 in Example 2 were measured using ultraviolet photoelectron spectroscopy (UPS). The test results are shown in Figure 3 . As Figure 3 shown, the energy levels of the polymers TM1 and TM2 can better match the energy levels of perovskite compared to the traditional PTAA material.
[0248] (3) SEM test
[0249] The SEM cross-sectional comparison diagrams of the hole transport layers formed by the hole transport materials TM1 and TM2 in Example 1 and Example 2 and the perovskite layer were obtained by using an SEM tester. The test results are shown in Figure 4 . As Figure 4 shown, when preparing a perovskite thin film on the hole transport layer formed by TM1 or TM2 in this application, the cross-sectional holes are greatly reduced, and the crystallization quality of the film is significantly improved.
[0250] (4) Ultraviolet absorption test
[0251] The ultraviolet absorption spectra of the hole transport materials TM1 and TM2 were obtained by using a UV-vis tester. The test results are shown in Figure 5 . As Figure 5 shown, compared with the PTAA material, there is a certain red shift in the ultraviolet absorption of TM1 and TM2.
[0252] (5) Infrared spectrum test
[0253] The FTIR tester test shows that the N-H stretching vibration peak of the hole transport material TM1 in Example 1 is redshifted by 120 cm⁻¹, confirming that the amino group and the thiocarbonyl group form an intermolecular N-H···S=C hydrogen bond network, and the crystallinity of the film is significantly improved.
[0254] (6)Photovoltaic performance test
[0255] Place the solar cells fabricated in the above examples and comparative examples in a solar simulator (manufacturer: Wavelabs), under the irradiation of one sun intensity, apply a bias voltage (Vp, the bias voltage range is -0.1 to 1.2 V) to the device with a test source meter and measure the output current of the device to obtain the bias voltage-current density curve.
[0256] Open-circuit voltage (Voc): The terminal voltage of the cell when no load is connected, that is, the bias voltage value when the current density in the bias voltage-current density curve is 0 mA·cm -2 at this time.
[0257] Short-circuit current density (Jsc): The output current when the cell is short-circuited per unit area, that is, the current density when the bias voltage is 0 V in the bias voltage-current density curve.
[0258] Fill factor (FF): FF = max(Vp × Jsc),
[0259] where Vp is the bias voltage and Jsc is the short-circuit current density.
[0260] Photovoltaic cell efficiency (PCE): PCE = Voc × Jsc × FF.
[0261] The test results of the above performances are shown in Table 1, Figure 6 and Figure 7 as shown.
[0262] Table 1
[0263]
[0264] As shown in Table 1, Figure 1 , Figure 6 and Figure 7 as shown, by comparing Examples 1 to 12 and Comparative Examples 1 to 2, it can be seen that the hole transport material provided by the present application improves the wettability of the perovskite solution, and the device performance of the perovskite solar cell is greatly improved.
[0265] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope described in this specification.
[0266] The above-described embodiments merely represent several implementation manners of the present application. Their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the patent of the present application. It should be noted that for those of ordinary skill in the art, without departing from the technical concept of the present application, several modifications and improvements can still be made, and these all fall within the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the appended claims.
Claims
1. A hole transport material, characterized in that, Comprising a hole-transporting polymer, the hole-transporting polymer having a repeating unit represented by formula (I): Formula (I); In formula (I): * represents a bonding site; Y represents a single bond, a sulfur atom, an oxygen atom, a nitrogen atom, or is absent; X represents a single bond, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted aryl group having 5 or 6 ring-forming atoms, or a substituted or unsubstituted heteroaryl group having 5 or 6 ring-forming atoms.
2. The hole transporting material according to claim 1, wherein The X is selected from one of the following structures: 、 、 、 、 、 、 。 3. The hole transporting material according to claim 1, wherein The hole-transporting polymer is a homopolymer formed by the repeating unit represented by formula (I).
4. The hole transport material according to any one of claims 1 to 3, characterized in that The hole-transporting polymer satisfies at least one of the following conditions: (1) In the hole-transporting polymer, the number of the repeating units represented by formula (I) is an integer from 3 to 100,000; (2) The weight-average molecular weight M of the hole-transporting polymer w is from 1000 g / mol to 2000000 g / mol.
5. A preparation method of a hole transport material, characterized in that, Comprising the following steps: S1. The dibromo aromatic amine compound successively undergoes nucleophilic substitution reactions with an N-(tert-butoxycarbonyl)-α-bromoamine compound and a thiocyanate to obtain an intermediate compound; S2. The intermediate compound undergoes a polymerization reaction to obtain a hole-transporting polymer; Wherein, the dibromo aromatic amine has a structure represented by formula (II): Formula (II); The N-(tert-butoxycarbonyl)-α-bromoamine compound has a structure represented by formula (III): Formula (III); The intermediate compound has a structure represented by formula (IV): Formula (IV); The hole-transporting polymer has a repeating unit represented by formula (I): Formula (I); In formulas (I)-(IV), * represents a bonding site; Y represents a single bond, a sulfur atom, an oxygen atom, a nitrogen atom, or is absent; X represents a single bond, a substituted or unsubstituted C1-C5 alkyl group, a substituted or unsubstituted aryl group having 5 or 6 ring-forming atoms, or a substituted or unsubstituted heteroaryl group having 5 or 6 ring-forming atoms.
6. The preparation method of the hole transporting material according to claim 5, wherein The step S1 specifically comprises the following steps: S11. The dibromo aromatic amine compound undergoes a nucleophilic substitution reaction with the N-(tert-butoxycarbonyl)-α-bromoamine compound to obtain a first intermediate; S12. The first intermediate removes the tert-butoxycarbonyl group under acid catalysis to obtain a second intermediate; S13. The second intermediate undergoes a nucleophilic substitution reaction with the thiocyanate to obtain a third intermediate, which is the intermediate compound; Wherein, the first intermediate has a structure represented by formula (V): Formula (V); The second intermediate has a structure represented by formula (VI): Formula (VI).
7. The preparation method of the hole transporting material according to claim 5, characterized in that, The step S2 specifically comprises the following steps: S21. The intermediate compound reacts with a tert-butoxycarbonyl protecting agent to introduce a tert-butoxycarbonyl group to obtain a fourth intermediate; S22. After the fourth intermediate undergoes a polymerization reaction, the tert-butoxycarbonyl group is removed under acid catalysis to obtain the hole-transporting polymer; Wherein, the fourth intermediate has a structure represented by formula (VII): Formula (VII).
8. The preparation method of the hole transporting material according to any one of claims 5 to 7, characterized in that, The polymerization reaction is carried out under the action of a nickel catalyst and a ligand.
9. A solar cell, characterized in that: Comprising a hole-transporting layer, the hole-transporting layer comprising the hole-transporting material according to any one of claims 1 to 4 or the hole-transporting material prepared by the preparation method according to any one of claims 5 to 8.
10. An optoelectronic device, characterized in that: Comprising a hole-transporting layer, the hole-transporting layer comprising the hole-transporting material according to any one of claims 1 to 4 or the hole-transporting material prepared by the preparation method according to any one of claims 5 to 8.